Piezoelectric Characteristics of LiNbO3 Thin-film Heterostructures via Piezoresponse Force Microscopy - D.A. Kiselev; S.V. Ksenich; R.N. Zhukov; A.S. Bykov; M.D. Malinkovich; V.V. Shvartsman; D.C. Lupascu; Yu.N. Parkhomenko (Журнал нано- та електронної фізики)
Electro-optic LiNbO3 thin films were deposited on Si(100) and Si(111) substrates using a radio-frequency magnetron sputtering process. The piezoelectric properties of the LiNbO3 films were investigated using the scanning probe microscopy in the piezoresponse mode. The obtained results show the high degree of grains orientation in polycrystalline structure. The piezoelectric modulus (dzz) was estimated to be 16 pm/V (for LiNbO3 / Si(100)) and 22 pm/V (for LiNbO3 / Si(111)) and the polarization about of 0.37 C·m – 2. These values are larger than those reported previously for LiNbO3 films.